What are the effects of proton pump inhibitors on the small intestine? - Fujimori, Shunji (World J Gastroenterol, 2015)
Generally, proton-pump inhibitors (PPIs) have great benefit for patients with acid related disease with less frequently occurring side effects. According to a recent report, PPIs provoke dysbiosis of the small intestinal bacterial flora, exacerbating nonsteroidal anti-inflammatory drug-induced small intestinal injury. Several meta-analyses and systematic reviews have reported that patients treated with PPIs, as well as post-gastrectomy patients, have a higher frequency of small intestinal bacterial overgrowth (SIBO) compared to patients who lack the aforementioned conditions. Furthermore, there is insufficient evidence that these conditions induce Clostridium difficile infection. At this time, PPI-induced dysbiosis is considered a type of SIBO. It now seems likely that intestinal bacterial flora influence many diseases, such as inflammatory bowel disease, diabetes mellitus, obesity, non-alcoholic fatty liver disease, and autoimmune diseases. When attempting to control intestinal bacterial flora with probiotics, prebiotics, and fecal microbiota transplantation, etc., the influence of acid suppression therapy, especially PPIs, should not be overlooked.